Identifying critical success factors for school improvement among excellent principals in high performing schools in Malaysia: A case study / Umar Man - Umar, Man (2018)
This study identifies through explorative investigations on the critical success factors (CSF) of school improvement. Literature review show two models commonly observed in the process of school improvement (a) the top-down and (b) the bottom-up models. However there are missing links to explain further between these models. Therefore this study proposes to identify the critical success factors under these two models. This study is designed with a descriptive, non-experimental approach while adopting the case study framework. The processes are set out in three stages sequenced into an exploratory-inquiry-observation for data collection and analysis. The exploratory investigation has identified three main principalship practices contributed towards school improvement efforts. These are (a) leadership (b) managements and administrations and (c) strategies. The inquiry method has been condensed through interviewing. The interviewees were selected through ï¿½critical samplingï¿½ approach among the population of principals. The approach is by identifying those excellent principals who are in the highest category according to their salary scales which is in the ï¿½JUSA Cï¿½ category. During the study there are only eight excellent principals out of the total number of 2354 principals in the countryï¿½s mainstream education system that are in this category. Out of these eight excellent principals six excellent principals formed the sample of this study. An open-ended questionnaire was used during the interviews. Qualitative data was analyzed using the (i) within-case analysis and (ii) cross-case analysis. For the qualitative approach thematic analysis was conducted using the three levels of coding process (i) open coding (ii) axial coding and (iii) selective coding. The results have identified a number of constructs that were clustered into (i) critical success factors and (ii) functional factors. The outcomes of these clustering showed that there are certain similarities and differences from among these excellent principals in their approaches towards school improvement. Observations further enhanced the validity and reliability of these critical success factors identified. Flanaganï¿½s ï¿½Critical-Incident Techniqueï¿½ (CIT) was used during the observation. It was to further establish these findings through evidences acquired contextually in high performing schools. The final results of all these findings are in support towards the critical success factors identified and the model developed. Firstly, it addressed the five research questions posited. Secondly, it confirmed that the proposition through the critical success factors model developed is significant and relevant to the needs. Thirdly, the study concludes that the model developed has empirically proven of its potentials. This model can enable principals to lead school improvement more effectively.